“PSYCHOLOGICAL APPROACH” IN THE WORKS OF SHUKUR KHOLMIRZAYEV - Turdiqulov Kamronbek Muzaffar o'g'li (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: This article provides a psychological description of Shukur Kholmirzayev's works. Shukur Kholmirzayev's thoughts on the specific aspects of the characters in his works, including the love of life, aspiration, resistance to death, fighting spirit, etc. Adib has a special place in the rise of the Uzbek people's spirituality with his unique prose created with high artistic skills, psychological and emotional situations and feelings in his works.